Aiming to the superior of phosphor pattern: Influence of SiO2 nanoparticles on photoluminescence intensification of YAG:Ce - My Hanh Nguyen Thi; Thuc Minh Bui; Nguyen Doan Quoc Anh (International Journal of Electrical and Computer Engineering (IJECE), 2021)
Yttrium aluminum garnet (YAG: RE) rare-earth-doped phosphors have great photoluminescence (PL) characteristics and are commonly used in light-emitting rectifying tubes. The RE elements used in these phosphors, however, are precious and in shortage. The production of phosphorus containing a limited amount of RE content is therefore essential. One solution is to manufacture Nano composite phosphors that use an inexpensive and more easily available content as a matrix for RE oxide. In this research, we developed a YAG: Ce/SiO2 Nano composite using a sol-gel procedure; in order to impulse micelle formation and agglomeration, poly (ethylene glycol) and urea have been added, respectively. X-ray diffraction, scanning and transmission electron microscopy (TEM) and energy-dispersive X-ray spectroscopy were used to characterize the Nano composites. In proposing an explanation for this enhancement, we defined the concentration of SiO2 that produced optimum PL enhancement and used geometric models as well as the characterization consequences. Our results demonstrated that a 10% SiO2 concentration produced a 120% PL intensity of pure YAG:Ce. TEM analysis revealed that SiO2 nanoparticles filled the voids between the YAG:Ce crystals' single grain borders, hence inhibiting light scattering, resulting in increased PL. This procedure would be beneficial for the synthesis of low-RE and high-PL phosphors on a wide scale.